Proses Berpikir Komputasi Siswa dalam Menyelesaikan Soal Numerasi Konten Geometri dan Pengukuran Ditinjau dari Gaya Kognitif - Farida, Siti; Rahaju, Endah Budi (MATHEdunesa, 2025)
This study aims to describe the computational thinking processes of junior high school students with field independent (FI) and field dependent (FD) cognitive styles in solving numeracy problems in geometry and measurement content. This study uses a qualitative approach with descriptive analysis techniques. The research subjects were two students (one FI and one FD) of the same gender and with equivalent high mathematical abilities. Data were collected through the Group Embedded Figures Test (GEFT), AKM numeracy problems on geometry and measurement content, and interview guidelines. The results of the study indicate that FI students meet all five indicators of computational thinking, namely decomposition, pattern recognition, abstraction, algorithms and procedures, and generalization. Meanwhile, FD students only met three indicators: decomposition, abstraction, and generalization. These findings indicate that cognitive style influences the development of computational thinking skills, so teachers need to design appropriate learning strategies to support students with different cognitive styles in numeracy learning.